Science Diplomacy in Emerging Economies: A Phenomenological Analysis of the Colombian Case - Echeverría King, Luisa Fernanda; González, Diana Alejandra; Andrade-Sastoque, Ernesto (Frontiers in Research Metrics and Analytics, 2021)
Little has been investigated about Science Diplomacy (SD) in emerging economies, more specifically on governance schemes useful for organizing intersecting actors, practices, conceptions and suggestions of the future in foreign affairs and Science, Technology and Innovation (STI) in public administration sectors. This paper contributes to a better understanding of the “texture and nature” of SD initiatives in emerging economies through the eyes of relevant actors involved or reflecting about them in Colombia. The aim of this paper is to propose a general governance scheme for SD in emerging economies and its potential instrumentation for a policy-mix. In Colombia, SD initiatives are very fragmented, and are not part of the priorities of the Colombian state, however the increasing interest of an embryonic practitioner and scholar community working in the topic make necessary this work. A phenomenological perspective combined with a single case study research methodology is used to gain a very accurate description of the state of the situation of SD in Colombia. Policy document review and semi-structured interviews were conducted with 18 relevant actors to understand the conceptions, practices, and suggestions for the future of SD in Colombia. The study results show that SD actors in Colombia are scattered, practices strongly related to traditional cooperation diplomatic activities and the need to give a function to SD for capacity building, better global intermediation and the development of new knowledge, in particular promoting SD abilities in the scientific community. In addition, data expresses the need to cultivate a multi-stakeholder working group for such a purpose. The study reflects on the need of a policy mix for SD in emerging economies. It proposes a general governance scheme for it, a potential instrumentation founded on research participant future suggestions, and a set of practical recommendations and policy implications. Conclusions and further research questions are set, pointing out the importance of including non-conventional diplomacy actors and knowledge, and the need to inquire rationales behind possible SD policy mixes in the southern world.